2017
DOI: 10.18261/issn.2464-3076-2017-04-06
|View full text |Cite
|
Sign up to set email alerts
|

Omsorgssektoren som integreringsarena:

Abstract: SAMMENDRAG:Økt tilstrømming av mennesker med flukt-og innvandringsbakgrunn har aktualisert behovet for kunnskap om virkningsfulle integreringstiltak. I de senere årene har bruk av ordinaert arbeidsliv fått økt oppmerksomhet innen integreringsfeltet. Tiltak som bruker ordinaer arbeidsplass som opplaerings-og kvalifiseringsarena er imidlertid svaert forskjellige, fra ulike varianter av «arbeid først»-innganger hvor målet er å få flyktninger og innThis article is downloaded from www.idunn.no.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The compounds tested for transcriptional activation of gmAhrs in vitro were also tested ex vivo in liver slices using a similar concentration range as used in the in vitro transactivation assay (BNF presented in 62 ). Activation of the Ahr signalling pathway was assessed by measuring altered mRNA expression of cyp1a with qPCR.…”
Section: Activation Of the Ahr Signaling Pathway In Precision-cut Liver Slicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds tested for transcriptional activation of gmAhrs in vitro were also tested ex vivo in liver slices using a similar concentration range as used in the in vitro transactivation assay (BNF presented in 62 ). Activation of the Ahr signalling pathway was assessed by measuring altered mRNA expression of cyp1a with qPCR.…”
Section: Activation Of the Ahr Signaling Pathway In Precision-cut Liver Slicesmentioning
confidence: 99%
“…Ex vivo exposure assays with precision-cut liver slices (PCLS) and analyses of cyp1a expression. PCLS were prepared as described previously with some modifications (details in Supplementary material) 62 . Liver slices were exposed to TCDD (n=5), FICZ (n=6), B[a]P (n=6) and PCB126 (n=7) (DMSO 0.01%).…”
mentioning
confidence: 99%
“…Tension between conflicting goals may remain unresolved if actors focus sequentially on first one goal and then another, eschewing the need to deal with incompatibilities (Cyert and March, 2006). A study of the healthcare sector as an arena for integration (Eide et al, 2017) reviewed different models for successful inclusion in the labor market. The study found support for prioritizing measures that led to immigrants' formal qualifications to achieve secure and stable employment and providing employment with enough income for the participants during the process, thus attending to the goal of skilled workers and employment for all simultaneously.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Nursing homes were chosen because the healthcare sector is perceived and used as an arena for integrating immigrants (Eide et al, 2017). This sector is growing, and in the foreseeable future, will employ larger numbers of people (Ministry of Health and Care Services, 2013).…”
Section: Research Setting and Methodsmentioning
confidence: 99%
“…Bonoli (2010) identifiserer fire ulike aktiviseringsstrategier: forsterkning av insentiver, arbeidsstøtte eller jobbassistanse, arbeidsrettede kurs og videre kvalifisering. Eide et al (2017) mener at flere parallelle strategier kan avdekkes i ulike tiltak (Bonoli, 2010;Schøyen, 2016).…”
Section: Arbeidsinnkluderingunclassified